Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages (b) Socialist. Aneurin Bevan, who presents this Bill, is a good Socialist administrator. Is this measure, therefore, a good and workable socialist enactment? The answer to this question depends on whether you think Socialism can be achieved step by step. If you do, then you will probably have only two serious criticisms to make of the Bill as it now stands before the details (many of them most important) are filled in. The first will be the proposal to allow a member of the Service to carry on private practice at the same time. How can this be justified except on grounds of expediency? No-one pays a fee for the sheer joy of spending money, but because he believes that by so doing he will get something better than he would otherwise receive. If he does get preferential treatment, what is it that is being withheld from the public patients? If he does not get preferential treatment but only thinks he does, where is the morality in charging him for something for which he has already paid? Even more serious is the effect which the existence of private fee-paying patients will have on the public patient. Will he really believe that he is getting the best possible attention? Part-time private practice has obviously been a concession by Mr. Bevan to the B.M.A., and he has weakened the whole structure of his Bill by making it. Nor, viewing the intensity of the campaign being carried on by the B.M.A., can he feel that his Bill would have received a much worse reception from that body had he insisted on doctors being either wholly inside or outside the Service. Laudable as is its intention, the decreasing capitation rate will cause grave doubts. For at least five and probably ten years, there are not going to be enough doctors to render all the services that are required. This means that doctors already practising must go on working excessive hours to give their patients adequate attention. The decreasing capitation rate combined with a basic salary leaves him free to decide how many patients he will attend, but weakens his present incentive to deal with the maximum number of which he is capable ; yet this proposal is being put to a body of people who, collectively at any rate, have not shown themselves to be filled with enthusiasm to demonstrate the virtue of the new Service. This will put a great strain on the humanitarian instincts of the doctors to see that no-one is denied attention. Common Wealth, however, has no faith in the Labour Party's policy of gradualism. While acknowledging that the Bill is much 14 15X/2/98/21